Inhibition of Nitric Oxide and Tumour Necrosis Factor-alpha Production in Peritoneal Macrophages by Aspergillus nidulans Melanin - Ribeiro Goncalves, Rita de Cassia; Kitagawa, Rodrigo Rezende; Goncalves Raddi, Maria Stella [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Pombeiro-Sponchiado, Sandra Regina (Pharmaceutical Soc Japan, 2013)
The naturally occurring pigment, melanin is found in organisms of all phylogenetic kingdoms, including fungi, and exhibits a wide range of biological activities. Our objective was to investigate the effects of melanin extracted from the fungus Aspergillus nidulans on the production of the pro-inflammatory mediators nitric oxide (NO) and tumour necrosis factor-alpha (TNF-alpha) in peritoneal macrophages and on the viability of McCoy mouse fibroblasts. The results showed that A. nidulans melanin did not stimulate NO production in macrophages, but it inhibited the NO production in lipopolysaccharide (LPS)-stimulated macrophages by approximately 82%. Similarly, A. nidulans melanin inhibited LPS-stimulated TNF-alpha production by 52% and showed a slight stimulatory effect on TNF-alpha production in macrophages. In addition, the toxicity of A. nidulans melanin to McCoy cells was much lesser (IC50=373.5 +/- 2.4 mu g/mL) than that of known agents such as cisplatin (IC50=41.2 mu g/mL). The viability of peritoneal macrophages was greater than 90% at the highest melanin concentration tested (100 mu g/mL). Thus, the combination of low cytotoxicity and marked inhibition of TNF-alpha and NO production suggests that A. nidulans melanin has potential as an anti-inflammatory agent and may be used in the future for development of new drugs with therapeutic utility.
Keywords: Aspergillus nidulans; melanin; nitric oxide; tumour necrosis factor-alpha; fungus